(3GdGUhd GdYdejI h GdYedjIs - (3ZGdH YhV(B, (3GdQaGYjs ((3YeGf(B:s (3OGQ GdjGRhQj(B,s, 2010)
(3GdeNRhf , GdQbGHI GdOGNdjI h GdJShjI GdHfcjI , GdeOjfhf h ChQGb GdbHV , eMGSHI GdGUhd GdKGHJIh GdeUGOQ GdWHjYjI h GdCUhd ZjQ GdedehSI , GdGSJKeGQGJ GdeGdjI , GdNUhe GdeJOGhdI (B.s
(3eQGLY U(B.389 (3; edGMb U(B.391s
Keywords: (3GdGSJKeGQGJ GdeGdjIs; (3GdQbGHIs; (3GdeGdjIs; (3GdeMGSHIs